Jakość governance: z doświadczeń gospodarek azjatyckich - Pęciak, Renata (The Quality of Governance: Asian Economies Experiences, 2009)
Contemporary global system attaches great importance to the idea of governance. This concept describes existent relations between government and society, characterizes the process by which governments are selected, monitored and replaced and explains the way of making decisions concerning political issues. The poor governance is one of the main reasons of potential crises so the imperative of good governance guarantees the balanced development of economies. The article in a very general way takes notes of some elements connected with the system of implementation governance rules in Asian economies. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 779-786